Oral health of pregnant women and possibilities for improving oral health prophylaxis in Lithuania - Juknienė, Jolita; Šimėnaitė, Gabrielė; Mockevičienė, Birutė (Central European journal of public health, 2025)
OBJECTIVES: The aim of the study was to identify potential areas for improvement in the prevention of oral diseases in pregnant women by assessing their oral care habits and awareness regarding oral health. METHODS: An original, anonymous, web-based survey was conducted among women at any stage of pregnancy. The survey consisted of 23 questions regarding oral care habits, knowledge about oral health of mother and child, general and oral health changes, and attendance of oral healthcare services during pregnancy. The data analysis was performed using IBM SPSS 27.0 version software. Descriptive statistics, Chi-square and Wilcoxon signed-rank tests were used to analyse the data. The level of statistical significance was set at p < 0.05. RESULTS: A total of 714 pregnant women participated in the study, with a mean (SD) age of 30.2 (4.4) years. Majority of the respondents demonstrated acceptable oral health-related knowledge and habits. A lack of interdental care among pregnant women was discovered. Nearly a third (27.6%) of the respondents reported a decline in their oral health during pregnancy. The most commonly reported general and oral health issues during pregnancy were increased stomach acid levels (71.3%) and gum bleeding (43.3%). Pregnant women were most frequently informed about the importance of oral care by an obstetrician-gynaecologist (25.4%). CONCLUSIONS: The study revealed the need for targeted interventions to enhance oral health awareness and practices among pregnant women in Lithuania. While overall oral hygiene habits were acceptable, deficiencies in interdental care and knowledge regarding oral health during pregnancy were evident. Higher level of education and urban residency were associated with superior oral care practices of pregnant women. In order to improve oral health of mother and child, interdisciplinary collaboration and dissemination of accessible, evidence-based information are essential.
Keywords: pregnancy; těhotenství; průzkumy a dotazníky; Oral Hygiene; Adult; health literacy; Health Knowledge, Attitudes, Practice; orální hygiena; prevention; Oral Health; ženské pohlaví; paediatric dentistry; těhotné ženy; Humans; Lithuania; Pregnancy; Surveys and Questionnaires; orální zdraví; Pregnant People; dospělí; zdraví - znalosti, postoje, praxe; Female; Litva; lidé; oral health